Preventing Severe COVID-19 with Tixagevimab-Cilgavimab in Hematological Patients Treated with Anti-CD20 Monoclonal Antibodies: An International Multicenter Study - Hovav Azuly; Tali Shafat; Daniel Grupel; Tzvika Porges; Ran Abuhasira; Ana Belkin; Ofir Deri; Yonatan Oster; Shadi Zahran; Ehud Horwitz; Netanel A. Horowitz; Hazim Khatib; et al. (Infectious Diseases and Therapy)
Abstract Introduction Despite the declining public health emergency status, COVID-19 still poses significant risks, especially for immunocompromised individuals. We aimed to evaluate the effectiveness of tixagevimab-cilgavimab (T-C) prophylaxis in preventing severe COVID-19 in patients with hematologic malignancies (HM) treated with anti-CD20 therapy during the early Omicron variant phase of the pandemic. Methods The European Society of Clinical Microbiology and Infectious Diseases Study Group for Respiratory Viruses (ESGREV) conducted a multicenter retrospective cohort study involving 15 centers from 5 countries. The study included 749 patients with HM treated with anti-CD20 between February 15 and June 30, 2022, comparing 215 who received T-C prophylaxis to 534 who did not. Results The study revealed a significant reduction in the risk of COVID-19 among patients who received T-C prophylaxis compared to those who did not (11.2% vs 23.4%, p < 0.001), with hazard ratio (HR) of 0.40 (95% CI 0.26–0.63), adjusted for age, sex, vaccination status, baseline HM malignancy and type of anti-CD-20. We also demonstrated a reduction for severe-critical diseases within all study populations, 1.4% vs 5.2%, p = 0.017, HR 0.26 (95% CI 0.08–0.84). Conclusion T-C prophylaxis effectively prevented COVID-19 and severe-critical COVID-19 in patients with HM treated with anti-CD20 monoclonal antibodies during the early Omicron variant phase of the pandemic. Even though T-C is ineffective against current variants, these findings highlight the importance of additional protective measures and the continued development of monoclonal antibodies to protect immunocompromised individuals to mitigate the impact of COVID-19 and other respiratory viral diseases.